IMPLEMENTASI NETWORK ADDRESS TRANSLATION (NAT) MENGGUNAKAN KERIO CONTROL VERSI 7.4.1 DI PUSAT PENELITIAN BIOTEKNOLOGI – LIPI - Tutang, Tutang; Tutuko, Ario; Rosyidin, Khoirur (BACA: Jurnal Dokumentasi dan Informasi, 2025)
Biotechnology Research Center as an institution engaged in the research, the need for data and updated information is an absolute thing. This requirement can be met one of them is the use of information technology either by using the internet. With the increasing number of Internet users in Biotechnology Research Center and order for all users who are members of the Local Area Network (LAN) can utilize the internet needed a good network management. While, during the network management Indonesian Institute of Sciences (LIPI), under the supervision of the Joint Network Team (TGJ – LIPI ) only provide one local IP segment which is limited to only 250 users. While number of internet users in Biotechnology Research Center and more than that number will continue to grow. To overcome these problems, then the LAN network at the Research Center for Biotechnology service facility utilizes Network Address Translation (NAT) contained in Kerio Control software version 7.4.1. The subject of this article is limited to the implementation and configuration of NAT using Kerio Control 7.4.1 version. From these results, we concluded that the implementation of NAT helps all users in the network LAN Biotechnology Research Center get Public IP, so that it can connect to the internet properly.